To translate the line given by the equation \( y = 3x + 2 \) one unit to the right and two units up, we can follow these steps:
-
Translating one unit to the right: To shift a function to the right, we replace \( x \) with \( x - 1 \). This gives us the new equation: \[ y = 3(x - 1) + 2 \] Simplifying this: \[ y = 3x - 3 + 2 = 3x - 1 \]
-
Translating two units up: To shift the function up, we add 2 to the entire equation: \[ y = (3x - 1) + 2 = 3x + 1 \]
Thus, the equation of the new line after the translation is: \[ y = 3x + 1 \]
So the correct response is: y = 3x + 1.